Simultaneous Optimization of Elastic-Plastic Building Structures and Viscous Dampers Under Critical Double Impulse - Akehashi, Hiroki; Takewaki, Izuru (Frontiers in Built Environment, 2020)
A new method for simultaneous optimal design of main building structures and viscous dampers is proposed for elastic-plastic multi-degree-of-freedom (MDOF) building structures subjected to the critical double impulse which is regarded as a representative of the main part of near-fault ground motions. The critical double impulse is characterized by the maximum energy input to the total system by the second impulse and the sum of the restoring force and the damping force in the first story attains zero by this critical input. The objective function is the maximum interstory drift along the building height. The original optimization problem is transformed into a problem of removing the most inactive story stiffness and damper damping coefficient. An efficient sensitivity-based design algorithm is developed for this simultaneous optimal design problem of main building structures and viscous dampers. It is pointed out that the order of changes of structural stiffness and damper damping magnitude is critical to the achievement of reasonable designs and cycle-by-cycle alternating redesign of story stiffness and damper damping coefficient is effective for its achievement. The double impulse pushover (DIP) analysis proposed in the previous paper (Akehashi and Takewaki 2019) for determining the input velocity level of the critical double impulse is also conducted to disclose the response characteristics of the designed building structures and dampers. It is shown that the proposed design method enables the high yield-strength design with effective seismic energy absorption and the high limit-strength design effective for extremely large disturbances. The distributions of the maximum acceleration responses in an initial design and the final design are also presented for the one-cycle sine wave corresponding to the critical double impulse.